They just don’t get it: a qualitative study on perceptions of anticipated self-injury stigma across generations - Stephen P. Lewis; Gabrielle A. Lucchese-Lavecchia; Nancy L. Heath; Rob Whitley (BMC Psychiatry)
Abstract Background Non-suicidal self-injury (NSSI) is a common and serious mental health concern among young adults. It is also highly stigmatised, which can impede disclosure and recovery. To advance the literature on NSSI stigma, we explored what young adults who self-injure believe different age-groups (i.e., young adults, parents, middle-aged, and older adults) think about NSSI and people who self-injure. Method Participants (n = 187) with a mean age of 19.07 (SD = 1.52) took part in an online survey and answered open-ended questions about the above beliefs. Responses were examined via reflexive thematic analysis. Results Findings yielded three primary themes namely: They Just Don’t Get It, Ignorance is Bliss, and Willing to Lend a Helping Hand. Overall, our results indicate that all age-groups asked about are believed to harbour stigmatising views (e.g., NSSI is selfish and attention-seeking, people who self-injure are weak and crazy). Perceptions regarding the prominence of these beliefs, however, varied across age-groups. Conclusion Expectancy beliefs and differences in anticipated stigma across age groups may stem from prior experiences with others and may play a role in disclosure. The present findings thus have implications for research, anti-stigma initiatives, and supportive practices.